Cloudy with a chance of meatballs - Barrett, Judi; Barrett, Ron (New York : Aladdin Books ; London : Collier Macmillan, 1978)
Life is delicious in the town of Chewandswallow where it rains soup and juice, snows mashed potatoes, and blows storms of hamburgers--until the weather takes a turn for the worse.
K
600
K
Keywords: Weather -- Fiction; Food -- Fiction